History, materiality and social practice: Spatial discourse analysis of a contemporary art museum in China. Issue 4 (December 2022) - Ravelli, Louise; Wu, Xiaoqin
This article explores the challenge of incorporating longer historical time frames into a social semiotic understanding of meaning-making. We focus on museums as complex, multimodal assemblages, and trace the distinct trajectory of museums and their development in China. We illustrate the key differentiating stages of museums in China, and focus on the contemporary Chengdu Tianfu Art Museum (hereby TAM), as a case study exemplifying the intertwined nature of history in aspects of contemporary museum practice. We argue that history is inherently intersected in the making of materiality and meaning, and demonstrate through illustrative Spatial Discourse Analysis how this intersection is materialized in the design and use of TAM. Our analysis shows that TAM is both continuous with, and different from, prior museum practices. In doing so, we reveal connections between semiotic change and social change, and demonstrate that history and materiality cannot be divorced from the politics of representation.